El cariotipo de Chaetanthera renifolia (J. Remy) Cabrera (Asteraceae) - Baeza, Carlos M.; Ruiz, Eduardo; Torres-Díaz, Cristian (Gayana Botánica, 2010)
The karyotype of Chaetanthera renifolia (J. Remy) Cabrera from Chile was examined. The species has 2n = 2x = 44 chromosomes, with 1m + 1st + 2st-sat + 17t + 1t-sat chromosomes. The reported karyotype is bimodal and very asymmetric (AsK % = 86.6, TF % = 13.4 and Syi % = 15.5). These results are indicating that this species has the highest known chromosome number of the genus so far and the most asymmetrical karyotype of the group.